Use of Artificial Intelligence For Brain Surgery - Jena, Somnath Prasad; Panigrahi , Souvagya (International Journal of Psychosocial Rehabilitation, 2019)
Artificial intelligence consciousness is both the knowledge of the machine, hardware and the part of Computer which intend to make it. Artificial intelligence has created numerous critical and noteworthy items even at this beginning time in its advancement. Albeit nobody can foresee the future in detail, obviously PCs with human-level knowledge would huge effect our regular daily existences and on the future course of development. Robot essentially goes about as a functioning specialist whose surrounding is the physical world the dynamic part precludes rocks, the artificial part precludes unadulterated programming operators or delicate bots, whose environment comprises of PC, document frameworks, database, and systems. In this project, the ideas of careful robots, how robotically helped cerebrum medical procedure performed and their advantages are discussed. The surgical robots are now being introduced in various operating rooms. Compared with a conventional medical procedure, Robotically-helped brain surgery is extremely valuable.